Designing InGaN/GaN nano‐LED arrays for étendue‐limited applications. Issue 4 (12th February 2015) - Fox, Sophia; O'Kane, Simon; Lis, Szymon; Allsopp, Duncan
Abstract: This paper presents the far field results of a study by simulation using the finite‐difference time‐domain (FDTD) method of vertical light emitting diode structures with an incorporated ordered nanorod array in place of the typical surface roughened region. For a dipole placed directly below the centre nanorod in the FDTD model, highly collimated light is achieved by changing the radii of the nanorods, for a fixed array pitch, which we attribute mainly to Bragg diffraction. By changing the pitch only, higher diffraction orders are observed in the far field emission as the pitch is increased and a relative increase in the directionality of emission is predicted. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)